A Technical Review On Hyperthermia - Saranya.D2, D.Kaarthika1, (International Journal of Scientific Research and Management (IJSRM), 2015)
Hyperthermia has promising strategy to enhance apoptosis .The fundamental idea and the effects of heat oncancer cells are well known. However, the results obtained in therapy by hyperthermia (HT) alone have beenonly partially satisfactory. Treatment at temperatures between 40 and 44 °C is cytotoxic for cells in anenvironment with a low oxygen partial pressure and low pH, conditions that are found specifically withintumour tissues, due to insufficient blood perfusion. Under such conditions radiotherapy is less effective, andsystemically applied cytotoxic agents will reach such areas in lower concentration than in well-per fusedareas. Therefore, clinically it is preferred to use hyperthermia in combination with radiation therapy andchemotherapy. Hyperthermia can be applied by several methods: local hyperthermia by external or internalenergy sources; regional hyperthermia by perfusion of organs or limbs or by irrigation of body cavities; andwhole body hyperthermia. Which can be implemented by many heating methods, such as microwave,radiofrequency, laser and ultrasound. Number of studies have reported the combination of thermoradiotherapy.Fortunately, phase II, III clinical trials have demonstrated that hyperthermia combinationtherapy is beneficial for local tumour control and survival in patients with high-risk tumours of differenttypes. Consequently, much attention has been focussed on identifying agents among the conventionalchemotherapeutics substances that can sensitise tumour cells to hyperthermia-induced damage with minimaleffects on normal cells. In the review, we overviewed important mechanism of hyperthermia-inducedapoptosis and the substance which can act as heat sensitizers’ in cancer therapy.KEYWORDS: Hyperthermia, radiotherapy, chemotherapy, microwave,